2019
DOI: 10.1002/pros.23841
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation‐associated pathologies in a case of prostate schistosomiasis: Implications for a causal role in prostate carcinogenesis

Abstract: Background Urogenital infection with Schistosoma haematobium is a risk factor for the development of squamous cell carcinoma of the urinary bladder. The pathophysiology is thought to be mediated in part by inflammation, cellular damage, and bladder regeneration induced by the parasitic infection. Herein, we report an unusual case of schistosomiasis of the prostate that was found concurrent with prostate adenocarcinoma in a radical prostatectomy specimen from a man in the United States. Methods The infecting Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The elevated prostate-specific antigen levels we observed could have be attributed to old age, prostatitis, benign hyperplasia, urinary tract infections, ejaculation, prostate injury and medicine prolonged bicycles rides [ 43 ]. Prostatic inflammation due to S. haematobium or S. mansoni ova deposits can lead to elevated levels of systemic prostate-specific antigen levels [ 5 , 44 , 45 ]. Furthermore, other studies that reported prostatic schistosomiasis cases with high prostate-specific antigen levels were not associated with prostatic schistosomiasis cancer [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated prostate-specific antigen levels we observed could have be attributed to old age, prostatitis, benign hyperplasia, urinary tract infections, ejaculation, prostate injury and medicine prolonged bicycles rides [ 43 ]. Prostatic inflammation due to S. haematobium or S. mansoni ova deposits can lead to elevated levels of systemic prostate-specific antigen levels [ 5 , 44 , 45 ]. Furthermore, other studies that reported prostatic schistosomiasis cases with high prostate-specific antigen levels were not associated with prostatic schistosomiasis cancer [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is a common urogenital condition living in both schistosomiasis and non-schistosomiasis endemic areas. Despite geographical locations, coincidences of MGS infections and prostate cancer cases have also been reported in non-schistosome endemic areas [ 3 5 ]. The concurrent incidences of prostatic MGS and prostate cancer have prompted the suggestion of a causal association between the two diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate infections and inflammation are potential initiating factors in prostate cancer development (2)(3)(4)(5). Specifically, prostate infection or other inflammatory stimuli may drive the formation of proliferative inflammatory atrophy (PIA), a putative prostate cancer precursor lesion (6)(7)(8). The atrophic luminal epithelial cells in PIA are markedly proliferative compared to that of normal-appearing epithelium, are enriched with cells of an intermediate phenotype that have properties of both basal and luminal epithelial cells (9), and are sometimes observed in direct transition with prostatic intraepithelial neoplasia (PIN, the most accepted direct precursor to prostate cancer) and adenocarcinoma (10).…”
mentioning
confidence: 99%